Blood Flow Simulation and Applications - Luísa Costa Sousa (2012)
In the vascular system altered flow conditions, such as separation andflow-reversal zones play an important role in the development of arterial diseases.Nowadays computational biomechanics modeling is still in the research and developmentstage. This chapter presents a numerical computational methodology forblood flow simulation using the Finite Element method outlining field equations andapproaches for numerical solutions. Due to the complexity of the vascular systemsimplifying assumptions for the mathematical modeling process are made. Twoapplications of the developed tool to describe arterial hemodynamics are presented,a flow simulation in the human carotid artery bifurcation and a search for anoptimized geometry of an artificial bypass graft.